2021
DOI: 10.1186/s12935-021-01806-1
|View full text |Cite
|
Sign up to set email alerts
|

Ring finger protein 152-dependent degradation of TSPAN12 suppresses hepatocellular carcinoma progression

Abstract: Background Hepatocellular carcinoma (HCC) is the third cause of cancer death in the world, and few molecularly targeted anticancer therapies have been developed to treat it. The E3 ubiquitin ligase RNF152 has been reported to regulate the activity of the mechanistic target of rapamycin complex 1 (mTORC1), induce autophagy and apoptosis. However, the relationship between RNF152 and HCC is unclear. Methods Transcriptome RNA-sequencing data of HCC sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Moreover, RNF183 could confer resistance to trametinib in colorectal cancer and promote the metastasis (Geng et al, 2017). In contrast, RNF152 could suppress the proliferation of hepatocellular carcinoma and was a prognostic biomarker for colorectal cancer (Cui et al, 2018; Wan et al, 2021). Ding et al reported that RNF150 was associated with the risk of COPD patients (Ding, Niu, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RNF183 could confer resistance to trametinib in colorectal cancer and promote the metastasis (Geng et al, 2017). In contrast, RNF152 could suppress the proliferation of hepatocellular carcinoma and was a prognostic biomarker for colorectal cancer (Cui et al, 2018; Wan et al, 2021). Ding et al reported that RNF150 was associated with the risk of COPD patients (Ding, Niu, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“… 59 Additionally, TSPAN12 has been reported to be a proliferation‐promoting regulatory factor in a variety of neoplastic diseases, including small‐cell lung carcinoma, non‐small cell lung carcinoma, ovarian cancer, and hepatocellular carcinoma. 41 , 60 , 61 , 62 Furthermore, TSPAN12 functions as an important regulator of retinal vascular development by promoting Norrin‐induced FZD4/beta‐catenin signaling. 63 Previous studies combined with our results suggest that AQP1 and TSPAN12 are expected to be potential proliferation markers for SOX2‐positive RSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there exists a correlation between the aquaporin expression profile and neural differentiation 59 . Additionally, TSPAN12 has been reported to be a proliferation‐promoting regulatory factor in a variety of neoplastic diseases, including small‐cell lung carcinoma, non‐small cell lung carcinoma, ovarian cancer, and hepatocellular carcinoma 41,60–62 . Furthermore, TSPAN12 functions as an important regulator of retinal vascular development by promoting Norrin‐induced FZD4/beta‐catenin signaling 63 .…”
Section: Discussionmentioning
confidence: 99%
“…RNF152 acts as a positive regulator of TLR/IL-1Rmediated signaling by promoting oligomerization of MyD88 [14]. Additionally, RNF152 targets TSPAN12 for ubiquitination and subsequent proteasomal degradation, resulting in the suppression of hepatocellular carcinoma cell proliferation [15]. RNF152, along with RNF182, RNF183, and RNF186, constitutes the RNF183 family, consisting of closely related genes encoding a RING-finger domain (C3HC4) at their N-terminus and one or two predicted transmembrane domains at their C-terminus with high homology [16].…”
Section: Introductionmentioning
confidence: 99%